THE IMPLEMENTATION OF THE PROBLEM BASED LEARNING MODEL TO IMPROVE STUDENTS’ MATHEMATICAL PROBLEM-SOLVING ABILITY IN PHASE D ON SOCIAL ARITHMETIC CONTENT - Wahyuni Sabrina; Armis; Sehatta Saragih (Jurnal Prinsip Pendidikan Matematika, 2025)
This study was motivated by the low mathematical problem-solving ability (MPSA) of students in class VIII.1 at SMPN 35 Pekanbaru. This condition was caused by teacher-centered learning, the lack of problem-based exercises, and low student engagement in the learning process. The results of the initial test indicated that students’ MPSA achievement on each indicator was still categorized as low. This study aimed to improve students’ MPSA and enhance the quality of the learning process through the implementation of the Problem Based Learning (PBL) model in social arithmetic material. The method used was Classroom Action Research (CAR), with students of class VIII.1 at SMPN 35 Pekanbaru in the even semester of the 2023/2024 academic year as the research subjects. The PBL model was implemented through several stages, namely problem orientation, investigation, development and presentation of results, and evaluation of the problem-solving process. The implementation of this model is aligned with the indicators of MPSA, including understanding the problem, planning a solution, carrying out the plan, and interpreting the results. The results showed that before the intervention, the average MPSA score of students was 30.49, categorized as “beginning to develop.” After the implementation in Cycle I, the average score increased to 40.09, and further improved to 52.1 in Cycle II, categorized as “adequate”. In conclusion, the implementation of the PBL model in the learning process was able to improve the quality of instruction and enhance students’ mathematical problem-solving ability.